Virtualization of spectrum for mobile operators: the pricing issue - Naldi, Maurizio; Mastroeni, Loretta (Electronic Communications of the EASST, 2011)
Though wireless spectrum is an untangible resource, it is typically assigned through licenses on a long-term basis and may be likened to a property of the licensee. The possibility to lease it temporarily through a secondary market makes it a virtualizable resource, exploitable by virtual operators. A crucial issue for the business propositions of virtual operators is spectrum pricing. Spectrum leasing may take place in spot markets, where the sale is conducted in a single step, or through a reservation process, with a two-stage mechanism aiming at protecting the prospective buyer against the price ﬂuctuations of the spot market. In spot markets the price is set either through auctions or by direct imposition by the license holder, with the aim of maximizing its revenues. In reservation procedures, the price can instead be set as a fair price through the no-arbitrage principle.